Leishmania amazonensis resistance in murine macrophages: Analysis of possible mechanisms. - Sandy Santos-Pereira; Flávia O Cardoso; Kátia S Calabrese; Tânia Zaverucha do Valle (PLoS ONE)
Leishmaniasis encompass a group of infectious parasitic diseases occurring in 97 endemic countries where over one billion people live in areas at risk of infection. It is in the World Health Organization list of neglected diseases and it is considered a serious public health problem, with more than 20,000 deaths a year and high morbidity. Infection by protozoa from the genus Leishmania can cause several forms of the disease, which may vary from a self-healing ulcer to fatal visceral infection. Leishmania species, as well as host immune response and genetics can modulate the course of the disease. Leishmania sp are obligatory intracellular parasites that have macrophages as their main host cell. Depending on the activation phenotype, these cells may have distinct roles in disease development, acting in parasite control or proliferation. Therefore, the purpose of this work was to analyze Leishmania amazonensis infection in primary macrophage cells obtained from mice with two distinct genetic backgrounds, ie. different susceptibility to the infection; evaluating the cause for that difference. After infection, peritoneal macrophages from the resistant C3H/He strain presented lower parasite load when compared to susceptible BALB/c macrophages. The same was also true when cells received a Th2 stimulus after infection, but the difference was abrogated under Th1 stimulus. Nitric oxide production and arginase activity was different between the strains under Th1 or Th2 stimulus, respectively, but iNOS inhibition was unable to suppress C3H/He resistance. Hydrogen peroxide production was also higher in C3H/He than BALB/c under Th1 stimulus, but it could not account for differences in susceptibility. These results led us to conclude that, although they have an important role in parasite control, neither NO nor H2O2 production can explain C3H/He resistance to infection. Other studies are needed to uncover different mechanisms of resistance/susceptibility to L. amazonensis.